Breakpoints of Gross Deletions Coincide with Non-B DNA Conformations - Bacolla, Albino; Jaworski, Adam; Larson, Jacquelynn E.; Jakupciak, John P.; Chuzhanova, Nadia; Abeysinghe, Shaun S.; O'Connell, Catherine D.; Cooper, David N.; Wells, Robert D.; Modrich, Paul L. (Proceedings of the National Academy of Sciences - PNAS, 2004)
Genomic rearrangements are a frequent source of instability, but the mechanisms involved are poorly understood. A 2.5-kbp poly(purine·pyrimidine) sequence from the human PKD1 gene, known to form non-B DNA structures, induced long deletions and other instabilities in plasmids that were mediated by mismatch repair and, in some cases, transcription. The breakpoints occurred at predicted non-B DNA structures. Distance measurements also indicated a significant proximity of alternating purine-pyrimidine and oligo(purine·pyrimidine) tracts to breakpoint junctions in 222 gross deletions and translocations, respectively, involved in human diseases. In 11 deletions analyzed, breakpoints were explicable by non-B DNA structure formation. We conclude that alternative DNA conformations trigger genomic rearrangements through recombination-repair activities.